2019
DOI: 10.5688/ajpe6821
|View full text |Cite
|
Sign up to set email alerts
|

Descriptive Analysis of Pharmacy Students’ Impressions on Virtual Interactive Case Software

Abstract: Objective. To assess students' impressions on whether Virtual Interactive Cases (VIC) contribute to their learning experience. Methods. Ten 4th year pharmacy students each independently completed the same four VIC cases followed by a semi-structured interview conducted by VIC project team members. The interviews were audio-recorded, transcribed, and coded for themes using qualitative research methods.Results. All participating students completed all of the cases. Overall, students' feedback on VIC was positive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…Although the 13 students represented approximately 10% (13/136) of all eligible students who were invited to participate, it was determined that data saturation occurred at the eighth participant, as no new themes were identified in subsequent interviews during data analysis. Themes derived from these interviews revealed some similarities to the original qualitative study 15 as they also found VIC software easy to navigate. Additional themes included: VIC enhances students' ability to identify relevant patient information; VIC accurately simulated hospital pharmacy practice, thereby helping to prepare students for their rotations; and students recommended an expanded role of VIC in the curriculum.…”
Section: Evaluation Of Vicmentioning
confidence: 70%
“…Although the 13 students represented approximately 10% (13/136) of all eligible students who were invited to participate, it was determined that data saturation occurred at the eighth participant, as no new themes were identified in subsequent interviews during data analysis. Themes derived from these interviews revealed some similarities to the original qualitative study 15 as they also found VIC software easy to navigate. Additional themes included: VIC enhances students' ability to identify relevant patient information; VIC accurately simulated hospital pharmacy practice, thereby helping to prepare students for their rotations; and students recommended an expanded role of VIC in the curriculum.…”
Section: Evaluation Of Vicmentioning
confidence: 70%
“…Some studies focused on dispensing and communication skills development [ 12 , 31 , 41 , 42 , 43 ], while others focused on the assessment of the knowledge, metacognition support, and promoting active learning, student confidence and independent studying [ 4 , 11 , 13 , 15 , 16 , 28 , 33 , 35 , 36 , 37 , 40 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 ]. Some literature focused more on presenting the CBS platform and students’ perceptions of it [ 34 , 38 , 39 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 ]. A few studies assessed the use of CBS platforms against other training methods [ 16 , 32 , 40 , 51 , 61 , 63 , 66 , 67 ].…”
Section: Resultsmentioning
confidence: 99%
“…Suh and Prophet (2018) reviewed more than 50 studies and reported that they offered realistic virtual reality experiences. Also, the literature has demonstrated that virtual environments can contribute to the transfer of learning (Makransky & Petersen, 2021), improved problem solving, communication, collaboration, application of knowledge, and methodological knowledge skills, and were considered a suitable environment for knowledge acquisition (Bravo et al, 2019) and practice (Gustafsson et al, 2017). Thus, it could be concluded that the instructional design principles of the VRPE would contribute to the aforementioned processes and could be used in various pharmacy education applications.…”
Section: Universal Designmentioning
confidence: 99%
“…Experiential learning is considered crucial in pharmacy education, with the Accreditation Council for Pharmacy Education (ACPE) even having emphasized the acquisition of clinical skills via experiential learning (ACPE, 2015). In pharmacy education, students develop their clinical reasoning skills through practice (Bravo et al, 2019). Furthermore, they are expected to acquire competent critical‐thinking, problem‐solving, and communication skills, therapeutic knowledge, and also skills in patient management (D'Souza et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation